Family values, social needs and preferences for welfare - Claudio Lucifora; Dominique Meurs (Institute for the Study of Labor (IZA), 2012)
This paper investigates the links between family values, social needs and individual preferences for welfare using data from the 2005 French Generation and Gender Survey (GGS). We analyse individual preferences, for financial assistance and the provision of care services, with respect to welfare support as opposed to within household production. The strength of family ties is based on individual's self-assessed family values (such as, duties, responsibilities and norms of reciprocity), both within the couple and between parents and children. We find a positive association between weak (strong) family values and the preferences for welfare state support (provision of domestic services). The relevance of family values is shown to be invariant to different socio-economic circumstances, such as: financial distress, bad health or family size. Using long term cultural determinants of selected ethnic and religious groups as instruments for family values, we also provide evidence for causal effects.
Keywords: J12; J13; I31; I38; 330; family values; preferences for welfare; culture; religion; Familiensoziologie; Soziale Werte; Sozialhilfe; Sozialstaat; Frankreich